Synthesis and Cytotoxic Potential of 3-Oxo-19β-trifluoroacetoxy-18αH-oleane-28-oic Acid - Elmira F. Khusnutdinova; Alexander I. Poptsov; Oxana B. Kazakova (Molbank, 2021)
Trifluoroacetic acid-promoted Wagner-Meerwein rearrangement of betulonic acid carboxamide led to the formation of the expected 19β,28-lactam along with a new germanicane-type 3-oxo-19β-trifluoroacetoxy-18αH-oleane-28-oic acid. The structure of this triterpenoid was confirmed by 2D NMR analyses. A primary evaluation of biological potency revealed an anticancer activity with GI50 < 5 μM against leukemia, colon cancer, breast cancer, and prostate cancer cell lines, while the parent compounds were not active.